Improving Learning Outcomes Reading Comprehension Using SQ3R Model - Vini Wela Septiana; Ambiyar; Ishak Aziz (CV. AFDIFAL MAJU BERKAH, 2021)
In this research, the writer used an action research. For collecting the data, the writer used test and observation. The data sources were the 4th grade SD Negeri 07 Padang which consists of 17 students and a Teacher as the observer. Cycle I consists of planning, action, observation and reflection. Cycle II added by the revision of cycle I. Based on the results of the research, The success in this research has increased from cycle to cycle. Where the results of the lesson plan of cycle I with an average of 82% (good), in the second cycle with an average value of 85% (very good), from the teacher aspect in the first cycle with an average value of 85% (very good), in the second cycle with the average value of 93% (very good), while in the aspect of the first cycle students with an average value of 63% (enough), in the second cycle with an average value of 93% (very good). The learning outcomes in this cycle indicate that the average value is 65% (enough), increasing in the second cycle with an average value of 82% (Good). Thus, the hypothesis in this research is acceptable. It means, there is a significant improving in using SQ3R to increase the students’ reading comprehension in SD Negeri 07 Padang. The study of conducting action research is invaluable and inspiring experience that gives the researcher new knowledge. It is hoped that action research can be implemented by other researchers to achieve a better teaching and learning process